2012
DOI: 10.3762/bjoc.8.191
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic tandem Michael addition reactions: A powerful access to the enantioselective synthesis of functionalized chromenes, thiochromenes and 1,2-dihydroquinolines

Abstract: SummaryEnantioselective organocatalysis has become a field of central importance within asymmetric chemical synthesis and appears to be efficient approach toward the construction of complex chiral molecules from simple achiral materials in one-pot transformations under mild conditions with high stereocontrol. This review addresses the most significant synthetic methods reported on chiral-amine-catalyzed tandem Michael conjugate addition of heteroatom-centered nucleophiles to α,β-unsaturated compounds followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(30 citation statements)
references
References 76 publications
(47 reference statements)
0
26
0
Order By: Relevance
“…5 mmol of 3 was dissolved in 15 mL methanol and then 5 mg CH 3 ONa was added and the solution was stirred for 24 h at room temperature. After 3 days (as monitored by TLC) the solvent was removed under reduced pressure, and the residue was recrystallized from ethanol to give pure 4 with yield 87 % (Scheme 4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 mmol of 3 was dissolved in 15 mL methanol and then 5 mg CH 3 ONa was added and the solution was stirred for 24 h at room temperature. After 3 days (as monitored by TLC) the solvent was removed under reduced pressure, and the residue was recrystallized from ethanol to give pure 4 with yield 87 % (Scheme 4).…”
Section: Methodsmentioning
confidence: 99%
“…The Michael addition of a stabilized carbon nucleophile or a heteroatom-centered nucleophile to electron-deficient olefins is a classical way to construct C-C or C-heteroatom bonds in organic synthesis [1][2][3][4][5]. Active methylene compounds (AMC) are widely used as carbon nucleophiles in the coupling with e.g., chalcone (1,3-diphenyl-2-propen-1-one) to form extended ketones (Scheme 1) [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Due to their versatile transformations in synthetic chemistry, a simple and efficient preparation of these valuable bulding blocks has drawn much attention from synthetic chemists. [4][5][6] The tandem oxa-MichaelHenry reaction of salicylaldehyde with β-nitrostyrenes is considered to be the most straightforward for preparation of 2-aryl-3-nitro-2H-chromenes. Several reports describe construction of 2-aryl-3-nitro-2H-chromenes in good yields using 1,4-diazabicyclo[2.2.2]octane (DABCO), 7,8 L-pipecolinic acid 9 or C 2 -symmetric pyrrolidine-triazoles 10 as catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Vildagliptin, a derivative of pyrrolidine has been employed to reduce hyperglycemia in type 2 diabetes mellitus [28][29][30]. Further, this has been reported that the pyrrolidine derivatives employed as organo-catalysts for many chemical reactions [31][32][33]. Dipipanone is a derivative of piperidine used as analgesic [34].…”
Section: Introductionmentioning
confidence: 99%